Living with the Florida Black Bear: a Homeowner's Guide to Nuisance Bear Prevention - Kimberly M. Annis; Melvin E. Sunquist; William M. Giuliano (EDIS, 2007)
WEC-215, a 3-page illustrated fact sheet by Kimberly M. Annis, Melvin E. Sunquist, and William M. Giuliano, describes the Florida black bear, its distribution, and the foraging behaviors that bring it in contact with humans, how to prevent nuisance problems with bears when in bear country, and what to do if you encounter a bear. Published by the UF Department of Wildlife Ecology and Conservation, February 2007.